Position-level forward kinematic singularities of RPRPR planar parallel robots - Karakaya, Levent (My University, 2023)
Paralel robotlar seri robotlara göre birçok dikkate değer avantaja sahiptir. Yüksek doğrulukta konumlama kabiliyeti ve yüksek yük/ ağırlık oranı bunların başlıcaları arasında sayılabilir. Ancak seri robotlardan farklı olarak, paralel robotların ileri kinematik çözümünde Tip II olarak bilinen tekillikler meydana gelir. Paralel robotların tekil konfigürasyonları klasik olarak hız düzeyindeki kinematik denklemlerde yer alan iki adet Jakobiyen matrisinin determinantı sıfıra eşitlenerek bulunur. Ancak paralel robotlar hız düzeyindeki ileri ve ters kinematik çözümlerin dejenere olduğu hareket tekilliklerine ilaveten pozisyon tekilliklerine de sahiptir. Paralel robotlar alanında oldukça güncel bir araştırma konusu olan pozisyon tekillikleri işbu tezin konusunu teşkil etmektedir. Tezin amacı, RPRPR düzlemsel paralel robotun ileri kinematik pozisyon tekilliklerini incelemektir. Bu amaç doğrultusunda belirlenen temel hedefler söz konusu robotun konum seviyesindeki ileri kinematik çözümünün dejenerasyonlarını tetkik etmek ve pozisyon denklemlerindeki bu dejenerasyonların ileri kinematik hareket tekillikleri ve yüksek mertebeden tekillikler ile olan ilişkilerini ortaya koymaktır. RPRPR düzlemsel paralel robot için, her ileri kinematik pozisyon tekilliğinin aynı zamanda bir ileri kinematik hareket tekilliği olduğu ve dahası, her ileri kinematik hareket tekilliğinin aynı zamanda bir ileri kinematik pozisyon tekilliği olduğu gösterilmiştir. Ayrıca, RPRPR düzlemsel paralel robotun herhangi bir Tip II tekilliğinin, robotun uç noktasının izlediği yolun eğimi bu tekillikte sıfırsa, yüksek mertebeden bir tekilliğe dönüştüğü gösterilmiştir.

Parallel robots have plenty of remarkable advantages over serial robots. Highly accurate positioning capability and high payload-to-weight ratio are among the main ones. Unlike serial robots, however, singularities known as Type II occur in the forward kinematics solution of parallel robots. Singular configurations of parallel robots are classically found by setting the determinants of the two Jacobian matrices in the velocity-level kinematic equations to zero. However, parallel robots also have position singularities other than the motion singularities at which forward and inverse kinematic solutions at the velocity-level degenerate. Position singularities, being a quite current research topic of parallel robots, constitute the subject of this thesis. The purpose of the thesis is to study the forward kinematic position singularities of the RPRPR planar parallel robot. The main objectives set for this purpose are to examine the degenerations of the position-level forward kinematic solution of the robot and to reveal the relations of these degenerations in the position equations with the forward kinematic motion singularities and high-order singularities. It is shown for the RPRPR planar parallel robot that every forward kinematic position singularity is also a forward kinematic motion singularity, and moreover, every forward kinematic motion singularity is also a forward kinematic position singularity. It is also demonstrated that any Type II singularity of the RPRPR planar parallel robot transforms into a high-order singularity if the slope of the endpoint path is zero at that singularity.
RPRPR düzlemsel paralel robotların konum düzeyinde ileri kinematik tekillikleri
Keywords: Makine mühendisliği; Mechanical engineering; Paralel manipülatörler; Paralel robotlar; Parallel manipulators; Parallel robots; Robotlar; Robots; Singularity; Tekillik